The anarchy of Nazi memorabilia: from things of tyranny to troubled treasure - Hughes, Michael (Material culture and modern conflict, 2022)
Out of the numerous books and articles on the Third Reich, few address its material culture, and fewer still discuss the phenomenon of Nazi memorabilia. This is all the more surprising given that Nazi symbols, so central to sustaining Hitler’s movement, continue to live long after the collapse of his 12-year Reich. Neither did Nazi ideology die; far-right populists would like to see the swastika flown over the White House or Buckingham Palace. Against a backdrop of right-wing extremism, military re-enactors think nothing of dressing up in Waffen-SS uniforms and romanticising the Third Reich in the name of living history. Auctioneers are prepared to hammer down Nazi artefacts to the highest bidder, but who is buying them, and why do they do so? Should collectors be allowed to decorate their homes with Nazi flags?